2008
DOI: 10.1111/j.1365-2486.2008.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Will European soil‐monitoring networks be able to detect changes in topsoil organic carbon content?

Abstract: Within the United Nations Framework

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 18 publications
7
96
1
1
Order By: Relevance
“…Despite the uncertainties mentioned above, error estimates for annual NEE in this study are within the range of errors presented for annual NEE estimates derived from EC measurements (30 to 50 g C m −2 yr −1 ) (e.g., Baldocchi, 2003;Dobermann et al, 2006;Hollinger et al, 2005) and below the minimum detectable difference reported for most repeated soil inventories (e.g., Batjes and Van Wesemael, 2015;Knebl et al, 2015;Necpálová et al, 2014;Saby et al, 2008;Schrumpf et al, 2011;VandenBygaart, 2006).…”
Section: Accuracy and Precision Of Applied Methodssupporting
confidence: 71%
“…Despite the uncertainties mentioned above, error estimates for annual NEE in this study are within the range of errors presented for annual NEE estimates derived from EC measurements (30 to 50 g C m −2 yr −1 ) (e.g., Baldocchi, 2003;Dobermann et al, 2006;Hollinger et al, 2005) and below the minimum detectable difference reported for most repeated soil inventories (e.g., Batjes and Van Wesemael, 2015;Knebl et al, 2015;Necpálová et al, 2014;Saby et al, 2008;Schrumpf et al, 2011;VandenBygaart, 2006).…”
Section: Accuracy and Precision Of Applied Methodssupporting
confidence: 71%
“…Recent research has shown that there is little change in soil carbon under permanent pasture (Hopkins et al, 2008), with the major changes being related to changes in land use (Smith, 2008). Soil monitoring networks exist across Europe, but they are unable to detect changes at a level of use to policy-makers (Saby et al, 2008). There is, therefore, considerable research activity in predicting changes in soil carbon in response to land-use change (e.g.…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…A major question, however, is whether SOC stock changes can be accurately quantified at regional to national scales to support effective policies (2). SOC inventory systems are being developed, but to date national-scale measurement-based inventories have not been able to clearly attribute changes in soil carbon stocks to specific land use and management and/or climate effects (3).…”
mentioning
confidence: 99%